2016
DOI: 10.1183/13993003.01016-2015
|View full text |Cite
|
Sign up to set email alerts
|

The independent role of prenatal and postnatal exposure to active and passive smoking on the development of early wheeze in children

Abstract: Maternal smoking during pregnancy increases childhood asthma risk, but health effects in children of nonsmoking mothers passively exposed to tobacco smoke during pregnancy are unclear. We examined the association of maternal passive smoking during pregnancy and wheeze in children aged ≤2 years.Individual data of 27 993 mother–child pairs from 15 European birth cohorts were combined in pooled analyses taking into consideration potential confounders.Children with maternal exposure to passive smoking during pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 45 publications
2
78
0
4
Order By: Relevance
“…Recently, a pooled analysis of 15 European birth cohorts demonstrated that children exposed to prenatal tobacco smoking and both pre- and postnatal tobacco smoking were more likely to develop wheeze up to the age of two years compared with unexposed children [11]. The available evidence regarding the independent and additive effects of both pre- and postnatal smoking exposure on the risk of wheeze in children is limited, however, particularly in Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a pooled analysis of 15 European birth cohorts demonstrated that children exposed to prenatal tobacco smoking and both pre- and postnatal tobacco smoking were more likely to develop wheeze up to the age of two years compared with unexposed children [11]. The available evidence regarding the independent and additive effects of both pre- and postnatal smoking exposure on the risk of wheeze in children is limited, however, particularly in Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies noted the importance of maternal smoking during pregnancy and the impact on the risk of asthma. [17][18][19][20][21] Smoking during pregnancy has been shown to increase the risk of preterm birth, which likely accounts for the difference of this confounder between the two cohorts in our study. 22,23 This confounder must be included in any study that assesses the association of preterm birth and asthma.…”
Section: Discussionmentioning
confidence: 92%
“…The risks are even higher when the mother shows pre-natal psychological stress [10]. It is known that wheezing may resolve spontaneously during childhood but may persist into adulthood, particularly in young children with severe asthma [11][12][13], but the question is, can we cut the risk or even prevent it?In this issue of the European Respiratory Journal, VARDAVAS et al [14] report the results of a pooled analysis of 15 cohort studies that participated in the European project ENRIECO (Environmental Health Risks in European Birth Cohorts) [15] to assess the independent effects of active and passive smoking exposure, both pre-and postnatal, on the development of wheeze in children before the age of 2 years. Furthermore, this study describes the development of wheeze in children based on the different sources of exposure and timeframes of pregnancy ( prenatal maternal active smoking, prenatal maternal passive smoking and children's postnatal passive smoking) and assessed them, both as independent and combined factors.…”
mentioning
confidence: 99%
“…Despite the underreported smoking prevalence figures in pregnant women, the methods used in reporting the effects of tobacco exposure in the development of wheeze also played a role. Relying on parental report for measuring outcomes such as wheeze may be subject to underreporting and recall bias, which is acknowledged by VARDAVAS et al [14] as a study limitations.…”
mentioning
confidence: 99%
See 1 more Smart Citation